Hubungan Kecepatan Waktu Pelayanan terhadap Kepuasan Pasien di Rumah Sakit Gigi dan Mulut Universitas Jember (The Relation of Speed Time Service to Patient Satisfaction in Rumah Sakit Gigi dan Mulut Universitas Jember) - Alifah Nur Jannah; Kiswaluyo .; Ristya Widi E.Y (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Background: Increasing number of health care providers triggered fierce competition among health care providers which cause any health care facilities should be put orientation on quality improvement and patient satisfaction. Dimensions can be used to measure the quality of health care is speed time service. Objective: To determine the relationship between the speed time service to patient satisfaction. Method: The study was observational analytic research with cross sectional survey design. The study was conducted by measuring the speed time service from registration until treatment completed using a stopwatch and measure the level of satisfaction by doing interviews with the guidelines Likert scale. Results were then tested Kolmogorov-Smirnov continued Spearman correlation test. Results and conclusions:The highest frequency for time registration is 49 % faster , 81 % speed waiting time is very fast , the speed at OD ( Oral Diagnosis ) 68 % very quickly and speed treatment time was 42 % . The level of patient satisfaction found 71 % of respondents were satisfied . Spearman correlation test results showed that there is a relationship between the speed time service to the patients satisfaction in RSGM Universitas Jember . Keywords: Patient satisfaction, RSGM Universitas Jember, speed time service.